Clinicopathological Investigation on Thiram Toxicosis in Broiler Chicken - Subapriya, S.; Vairamuthu, S.; Manohar, B. Murali; Balachandran, C. (International Journal of Poultry Science, 2007)
Thiram a fungicide used for treating corn and storing food grains were incorporated at 15, 30 and 60 ppm into the toxin free diet of broiler chicken for four weeks from the day of hatch. The clinical signs of tibial dyschondroplasia like reduced weight gain, lameness, abnormal bending of the tibial bones, enlarged hock joints and sternal recumbency were observed. The birds were sacrificed at the end of second and fourth week. Blood samples were collected for estimation of hematological parameters and sera separated for biochemical analysis. The packed cell volume and hemoglobin values were unaltered. Serum total proteins, albumin, globulin, albumin:globulin ratio, aspartate amino transferase, alanine amino transferase, alkaline phosphatase, gamma glutamyl transferase were unaltered. Hypercholesterolemia was observed in all the thiram fed birds and hypocalcemia and hypophosphatemia in the 60 ppm thiram fed birds.